ANALISIS DOWNTIME MESIN MIXER DENGAN BASIS INTERNET OF THINGS (IOT) TERHADAP EFEKTIVITAS PRODUKSI DI PT. SIGK (SINAR INDOGREEN KENCANA) - Awwalu Nanda Putra Fakinafiddin; M. Muslimin; Imaduddin BE (PT. Hasba Edukasi Mandiri, 2025)
The manufacturing sector in Indonesia plays a vital role in the economy, and one of the critical aspects of enhancing productivity is minimizing machine downtime. PT. Sinar Indo Green Kencana (SIGK) is a building materials manufacturing company facing challenges in the efficiency of its mixer machine, with an Overall Equipment Effectiveness (OEE) value of only 77.5%. This study utilizes Internet of Things (IoT) technology to monitor machine conditions in real-time and assess machine effectiveness using the OEE method. The research aims to identify the primary causes of downtime and develop predictive maintenance strategies to reduce losses due to machine failures. The findings reveal that high downtime is caused by unexpected breakdowns, lengthy setup times, and a lack of real-time monitoring. Therefore, using IoT to monitor downtime and OEE is crucial for improving machine efficiency and maintaining product quality. The research provides improvement recommendations that can be applied to enhance production effectiveness and minimize losses due to machine downtime.